Educación y escuela en el a\~no del bicentenario de Argentina historia reciente: Tucumán 1990/2010 - Liliana Macián de Barbieri (Atlantic Review of Economics, 2011)
– The paper provides a review of laws and other actions that have been undertaken in recent years in Argentina to improve education. Review is focused on the Province of Tucumán, where he studied education policy and some of their results. It analyzes the contents of the Federal Education Law No. 24,195, the Education Funding Law No. 26,075 and the National Education Law No. 26,206. Important laws of recent educational history and have proven to have power. It is emphasized that the Federal Law (1993) and National Law (2006) set extensions in the compulsory years of education reaching more people. Aimed at boosting both equity and quality in education. While the Finance Act (late 2005) was a powerful tool that served to increase resources for education, science and technology. Increases would be shared between the provinces and the nation. The study noted that over the years 90 and since 2003, after overcoming the strong socio-economic crisis facing Argentina in the provinces and the nation the authorities reacted to the state of education, making significant efforts to try to improve, that is of quality and compliance with the number of days of scheduled classes, which incorporate more of children and youth and lower age at school. And it is proposed to introduce new technologies. That in Tucumán, as in the other provinces, even serving more number of students, investment in education has grown in real terms, showing a considerable increase in spending per pupil in real wages of teachers.
Keywords: H52; I21; I22; 330; Bildungspolitik; Bildungsinvestition; Argentinien; Tucumán (Provinz)